Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conservation goals. One approach that shows considerable promise for addressing these challenges is adaptive management, which by now is broadly seen as a natural, intuitive, and potentially effective way to address decision-making in the face of uncertainties. Yet the concept of adaptive management continues to evolve, and its record of success remains limited. In this article, we present an operational framework for adaptive decision-making, and describe the challenges and opportunities in applying it to real-world problems. We discuss the key elements required for adaptive decision-making, and their integration into an iterative process that highlights and distinguishes technical and social learning. We illustrate the elements and processes of the framework with some successful on-the-ground examples of natural resource management. Finally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and strategic challenges.
Keywords: IMPORTANT

Aid on the Edge of Chaos: Rethinking International Cooperation in a Complex World - Ramalingam, Ben (Oxford University Press, 2014)
It is widely recognised that the foreign aid system - of which every country in the world is a part - is in need of drastic overhaul. There are conflicting opinions as to what should be done. Some call for dramatic increases to achieve longstanding promises. Others bang the drum for cutting it altogether, and suggest putting the fate of poor and vulnerable people in the hands of markets or business. A few argue that what is needed is creative, innovative transformation. The arguments in Aid on the Edge of Chaos are firmly in the third of these categories. In this ground-breaking book, Ben Ramalingam shows that the linear, mechanistic models and assumptions that foreign aid is built on are more at home in early twentieth century industry than in the dynamic, complex world we face today. The reality is that economies and societies are less like machines and more like ecosystems. Aid on the Edge of Chaos explores how thinkers and practitioners in economics, business, and public policy have started to embrace new, ecologically literate approaches to thinking and acting, informed by the ideas of complex adaptive systems research. It showcases insights, experiences, and dramatic results of a growing network of practitioners, researchers, and policy makers who are applying a complexity-informed approach to aid challenges. From transforming approaches to child malnutrition, to rethinking process of macroeconomic growth, from rural Vietnam to urban Columbia, Aid on the Edge of Chaos shows how embracing the ideas of complex systems thinking can help make foreign aid more relevant, more appropriate, more innovative, and more catalytic. It argues that taking on these ideas will be a vital part of the transformation of aid, from a post-WW2 mechanism of resource transfer, to a truly innovative and dynamic form of global cooperation fit for the twenty-first century.

Evaluating Complexity. Propositions for improving practice - Preskill, Hallie; Gopal, Srik (FSG, 2014)
9 propositions can help evaluators measure progress on complex social problems.
Keywords: IMPORTANT

Local Systems: a framework for supporting sustained development - USAID (USAID, 2014)

From best practice to best fit: understanding and navigating wicked problems in international development - Ramalingam, Ben; Laric, Miguel; Primrose, John (ODI, 2014)